2019
DOI: 10.1136/bjsports-2018-100168
|View full text |Cite
|
Sign up to set email alerts
|

Distinct effects of acute exercise and breaks in sitting on working memory and executive function in older adults: a three-arm, randomised cross-over trial to evaluate the effects of exercise with and without breaks in sitting on cognition

Abstract: BackgroundSedentary behaviour is associated with impaired cognition, whereas exercise can acutely improve cognition.ObjectiveWe compared the effects of a morning bout of moderate-intensity exercise, with and without subsequent light-intensity walking breaks from sitting, on cognition in older adults.MethodsSedentary overweight/obese older adults with normal cognitive function (n=67, 67±7 years, 31.2±4.1 kg/m2) completed three conditions (6-day washout): SIT (sitting): uninterrupted sitting (8 hours, control); … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
80
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(85 citation statements)
references
References 53 publications
3
80
1
1
Order By: Relevance
“…Time of day might also be an important moderator, but only several studies have examined whether time of day of engaging in a single bout of PA (e.g., morning, mid-day, afternoon, and evening/night) influences cognitive benefits [3]. Interestingly, Wheeler and colleagues observed that acute exercise in the morning, with or without subsequent breaks, resulted in greater working memory and executive function benefits [12] as well as greater increases in cerebral blood flow [13] over 8 h in older adults. This result, although observational, suggests that acute exercise in the morning might influence the brain for a longer period and benefit cognitive and brain health throughout the day.…”
Section: Optimizing Future Prescriptions Of Acute Exercise: the 3w1h mentioning
confidence: 99%
“…Time of day might also be an important moderator, but only several studies have examined whether time of day of engaging in a single bout of PA (e.g., morning, mid-day, afternoon, and evening/night) influences cognitive benefits [3]. Interestingly, Wheeler and colleagues observed that acute exercise in the morning, with or without subsequent breaks, resulted in greater working memory and executive function benefits [12] as well as greater increases in cerebral blood flow [13] over 8 h in older adults. This result, although observational, suggests that acute exercise in the morning might influence the brain for a longer period and benefit cognitive and brain health throughout the day.…”
Section: Optimizing Future Prescriptions Of Acute Exercise: the 3w1h mentioning
confidence: 99%
“…While evaluating the effects of non-exercise regimes (e.g. dynamic standing) on cognitive functioning and work productivity, transition states and thus multiple time-point testing of cognitive abilities should be considered [44].…”
Section: Discussionmentioning
confidence: 99%
“…Another study showed that activity breaks were detrimental to executive performance [42]. Wheeler and colleagues showed that a combination of morning exercise and breaking up sitting enhanced working memory but affected executive functions negatively [43]. Thus, more research is needed to address the effect of prolonged SB on cognitive functions.…”
Section: Discussionmentioning
confidence: 99%